CLOSED REDUCTION IN THE TREATMENT OF DISPLACED TIBIAL SPINE FRACTURES: REVISITING A LOST ART. Issue 4 (28th April 2020) - Ellis, Henry; Adkins, Morgan; Elliott, Marilyn; Huang, Sharon G.; Wyatt, Charles W.; Wilson, Philip
Background: There is renewed interest in optimal treatment, and development of algorithmic care for pediatric tibial spine fractures. While recent publications have most often investigated operative treatment, closed reduction of selected tibial spine fractures may result in good outcomes without invasive surgical procedures. Purpose: To evaluate an institutional series of displaced tibial spine factures treated with closed reduction for factors associated with treatment success. Methods: An IRB-approved, retrospective review of consecutive pediatric patients treated by a tertiary pediatric orthopedic group for displaced tibial spine fractures with closed reduction (2000 - 2017) was performed (Figure 1). Those with inadequate imaging or follow up were excluded. Demographics, injury data, exam findings, and reduction variables were recorded. Radiographic measures of fracture displacement pre and post-reduction, and at union were noted. Statistical comparison of variables associated with definitive closed reduction vs conversion to operative treatment was performed. Results: Of the 35 patients (mean age= 10.9 years [6-16 years]; 24 males) who underwent closed reduction of a tibial spine fracture, 19 (54.2%) had Type II Meyers and McKeever fractures, with the remainder Type III. Mean time to treatment was 6 days (2 hrs-46 days). Hemarthrosis aspiration with anesthetic injection was performed in 20 (57.1%) patients and 9 (25.7%) had general anesthesia or procedural sedation. Short-duration immobilization (typically 3 weeks) of long-leg casting (32, 91.4%) or bracing was utilized. The average reduction (Δ) in superior displacement of the tibial spine fragment was 4.6mm (0-16.4 mm) with 12 fractures improving > 5 mm following reduction maneuver. Eight patients (22.8%) failed closed reduction and were converted to operative fixation to treat residual displacement. Although no differences where noted in demographics, injury mechanism, classification (II vs III), or type of reduction; failures of closed reduction were noted to have more superior displacement (12.93 vs. 8.17 mm; p=0.023). Conclusion: Closed reduction of both Type II and Type III tibial spine fractures can result in acceptable reduction in in pediatric patients. Further prospective study of closed reduction of tibial spine fractures in selected patients presenting early, without critical meniscal pathology is warranted. : Figure 1. Imaging showing improvement of displacement of tibial spine fracture fragment in an 11 year-old male patient A. Pre-reduction x-ray B. Post-reduction fluoroscopic imaging in OR C. Seventeen days post-reduction x-ray D. Final x-ray 640 days post-reduction